Effect of polycystic ovary syndrome on increased risk of cardiovascular disease - Maciak, Anna; Pawłucki, Piotr; Cuper, Paulina; Sekuła, Michał; Dziurowicz, Błażej; Cuper, Michalina (Journal of Education, Health and Sport, 2023)
Introduction and purpose: Polycystic ovary syndrome (PCOS) is one of the most common endocrine disorders in women. It is a very complex disease in which hormonal disorders result in a number of metabolic dysfunctions and malfunctioning of the ovaries. This can lead to infertility, miscarriage and an increased risk of endometrial cancer. The aim of our work is to draw attention to the influence of PCOS on increased cardiovascular risk. Brief description of the state of knowledge: The occurrence of PCOS, especially uncontrolled pharmacologically and non-pharmacologically, may be associated with an increased cardiovascular risk. The literature describes a higher incidence of dyslipidemia, carbohydrate metabolism disorders, obesity, hypertension, chronic inflammation and oxidative stress. As a consequence, it can lead to the development of metabolic syndrome. All these factors negatively affect the risk of developing cardiovascular disease. To prevent this, it is necessary to use appropriate pharmacological and non-pharmacological methods in women diagnosed with PCOS. Conclusion: The mechanism of PCOS is complex and its development is influenced by genetic, endocrine, metabolic and environmental factors. The lack of proper diagnosis and the lack of treatment of PCOS is associated with numerous metabolic complications and an increased risk of cardiovascular diseases. Due to the poorly understood pathomechanism of this disease, further long-term studies are needed to help diagnose and treat PCOS.